Zwitterionic nanocapsules with pH- and thermal- responsiveness for drug-controlled release. (9th April 2023) - Sun, Zhijuan; Yang, Lei; Xu, Chenchen; Cai, Chenxin; Li, Li
Abstract: The construction of an environmentally responsive drug-release system is of great significance for the treatment of special diseases. In particular, the construction of nanomaterials with pH- and thermal-responsiveness, which can effectively encapsulate drugs and control drug release, is becoming hot research. In this study, zwitterionic nanocapsules with stable core–shell structures were synthesized by inverse reversible addition-fragmentation transfer miniemulsion interfacial polymerization. To further study the structure and performance of the nanocapsules, the prepared nanocapsules were characterized by transmission electron microscopy, dynamic light dispersion, and zeta potential analysis. It was found that the nanocapsules had dual pH- and thermal- responsiveness, and the average particle size ranged from 178 to 142 nm when the temperature changed from 25 °C to 40 °C. In addition, bovine serum albumin (BSA) was encapsulated into nanocapsules, and sustained release experiments were conducted at 10 °C and 40 °C. The results showed that nanocapsules as carriers of BSA could achieve the purpose of sustained release of drugs, and showed different sustained release curves at different temperatures. Finally, in vitro cytotoxicity tests were performed to demonstrate the feasibility of their biomedical application. It is believed that the dual pH- and thermal- responsive nanocapsules are promising for drug-controlled release.